Measuring the Sources of Taste-Based Discrimination Using List Experiments - Ariel Listo; Ercio A. Mu\~noz; Dario Sansone (Institute of Labor Economics (IZA), 2025)
This paper examines how attitudes among supervisors, co-workers, and customers are related to discrimination against sexual minority individuals in the workplace. Participants from a large, nationally representative online sample in Chile took part in double list experiments – which reduce social desirability bias when eliciting views on sensitive topics – followed by direct questions on attitudes toward sexual minority individuals. The findings reveal a discrepancy between reported and actual levels of comfort with gay individuals in the labor market. The respondents underreported their discomfort by 15-23 percentage points, with the largest bias and lowest comfort levels observed when they were asked about supervising gay employees. These attitudinal patterns were mirrored in incentivized donation behavior: individuals who chose not to donate any amount from a lottery to a local LGBTQ-related nonprofit reported lower comfort levels and exhibited greater misreporting. Finally, the respondents consistently underestimated the broader societal support for gay employees and co-workers.
Keywords: C93; D91; J15; J71; Z13; 330; discrimination; Chile; LGBTQ+